Adaptation Evolution and Phylogenetic Analyses of Species in Chinese Allium Section Pallasia and Related Species Based on Complete Chloroplast Genome Sequences. (12th June 2020) - Xie, Fu-Min; Xie, Deng-Feng; Xie, Chuan; Yu, Yan; Zhou, Song-Dong; He, Xing-Jin
Abstract : The section Pallasia is one of the components of the genus Allium subgenus Allium (Amaryllidaceae), and species relationship in this section is still not resolved very well, which hinders further evolutionary and adaptive studies. Here, the complete chloroplast genomes of five sect. Pallasia species were reported, and a comparative analysis was performed with other three related Allium species. The genome size of the eight species ranged from 151, 672 bp to 153, 339 bp in length, GC content changed from 36.7% to 36.8%, and 130 genes (except Allium pallasii ), 37 tRNA, and 8 rRNA were identified in each genome. By analyzing the IR/LSC and IR/SSC boundary, A. pallasii exhibited differences compared with other seven species. Phylogenetic analysis achieved high supports in each branch, seven of the eight Allium species cluster into a group, and A. pallasii exhibit a close relationship with A. obliquum . Higher pairwise Ka/Ks ratios were found in A. schoenoprasoides compared to A. caeruleum and A. macrostemon while a lower value of Ka/Ks ratios was detected between A. caeruleum and A. macrostemon . This study will be a great contribution to the future phylogenetic and adaptive research in Allium .